Fungal infection in repeat-breeder cattle and buffaloes - GIRI, A K; SHARMA, N C; SIKDAR, A (The Indian Journal of Animal Sciences, 2013)
Studies on fungal infection in repeat-breeder cattle (34) and buffaloes (33) were made. Animals were examined per rectum and the nature of estrual discharge, pus etc. were recorded. Aspergillus terreus and Chaetomium species were isolated from cattle, and Mucor sp. and Candida parapsilosis from buffaloes, rungal infection in repeat breeder cattle was 5.88% and in buffaloes 6.06% with an overall incidence of 5.97% in bovines.